If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(m + 1) = 54 Reorder the terms: 9(1 + m) = 54 (1 * 9 + m * 9) = 54 (9 + 9m) = 54 Solving 9 + 9m = 54 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 9m = 54 + -9 Combine like terms: 9 + -9 = 0 0 + 9m = 54 + -9 9m = 54 + -9 Combine like terms: 54 + -9 = 45 9m = 45 Divide each side by '9'. m = 5 Simplifying m = 5
| 3(s+22)+10=88 | | -12/r=-3 | | -c^2+c+30=0 | | -3(s+18)=-15 | | 6x+40=2x+4 | | 6(k-74)-5=83 | | 6=4-w | | x+17=5x+5 | | 6=-3(d-9) | | 2(7x+8)-4=28 | | 288=X+0.06X | | t-7/3=3 | | 4x+31=x+7 | | 12/n=3 | | 4x+11=x+1 | | 2/3x5/6x | | 8-51nx=3 | | 5x-26=x+6 | | x+(x*0.3)=5540.12 | | (x+(x*0.3))=5540.12 | | (X*.4)+X=4250 | | (2*.4)+X=4250 | | X*5+9=34 | | 9X*.40+X=4250 | | 6y=4y+24 | | 2X*.5=4250 | | x^3+x^2+x-20=0 | | 5x-12=-2+5 | | Y+1(33)-28=21 | | 10n+50=5n-25 | | 3y^2+2x-1=0 | | 3x-5x-120=0 |